(untitled) (Revista Inclusiones, 2020)
This paper reviews the features of the development of post-stress disorders in employees of the State Fire Service under the influence of occupational stress effects. The paper describes a general characteristic of personality traits that contribute to the development of post-stress disorders among employees of the State Fire Service. The novelty of this paper is associated with the study of the influence of character accentuations among employees of the State Fire Service on the development of post-stress disorders under the influence of occupational stress effects.